Electrolyte jet machining for surface texturing of Inconel 718 - Mitchell-Smith, Jonathon; Murray, J.W.; Kunieda, M.; Clare, A.T. (Saarland University, 2014)
Electrolyte jet machining is an emerging non-conventional machining process which is capable of selectively applying multi-scale surface textures. Surfaces processed in this way do not suffer from thermal damage and hence this technique is highly suited to finishing procedures in high value manufacturing across the aerospace and biomedical sectors. Furthermore, input variables can be modified dynamically to create functional graduation across component surfaces.